Exploration & discovery - "Man, John" (London; Belitha, 1990)
A look at the historical development of exploration and the different areas in which exploration has taken place and still takes place. This book, which is part of a series, covers mountains, jungles, under the seas and oceans, deep caves and the "final frontiers" of space.
Keywords: Discoveries in geography